2019
DOI: 10.1093/cercor/bhz103
|View full text |Cite|
|
Sign up to set email alerts
|

PTEN Activity Defines an Axis for Plasticity at Cortico-Amygdala Synapses and Influences Social Behavior

Abstract: Phosphatase and tensin homolog on chromosome 10 (PTEN) is a tumor suppressor and autism-associated gene that exerts an important influence over neuronal structure and function during development. In addition, it participates in synaptic plasticity processes in adulthood. As an attempt to assess synaptic and developmental mechanisms by which PTEN can modulate cognitive function, we studied the consequences of 2 different genetic manipulations in mice: presence of additional genomic copies of the Pten gene (Pten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 83 publications
0
35
0
Order By: Relevance
“…Moreover, chronic administration of the PTEN inhibitor bpV over 5 months to rTg4510 mice alleviated the synaptic and neuronal degeneration, as well as decreased microglial phagocytosis of synapses. Although several studies have shown that PTEN regulates synaptic density [29,40,67], our study is the first to reveal an involvement of PTEN in the process of synaptic elimination by microglia.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Moreover, chronic administration of the PTEN inhibitor bpV over 5 months to rTg4510 mice alleviated the synaptic and neuronal degeneration, as well as decreased microglial phagocytosis of synapses. Although several studies have shown that PTEN regulates synaptic density [29,40,67], our study is the first to reveal an involvement of PTEN in the process of synaptic elimination by microglia.…”
Section: Discussionmentioning
confidence: 56%
“…In support, we preserved levels of PSD-95 in rTg4510 mice after chronic treatment with the PTEN inhibitor bpV initiated prior to the occurrence of synapse loss. As the complement pathway functions in development and tauopathies to regulate synapse numbers [10,18,53,54], PTEN may function similarly in tauopathy as it also regulates synapse numbers during development [29,40,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary neurons in culture were prepared from E18 Sprague Dawley rat hippocampi as described by Sanchez-Puelles et al (2019). Hippocampi were dissected and dissociated using trypsin (0.25%) and DNase I (0.1 mg/ml) and further subjected to mechanical trituration.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it also plays a role in synaptic plasticity in adulthood. Studies have shown that the synaptic function of PTEN in amygdala is closely related to specific behavioral characteristics (47).…”
Section: Prepared Rehmannia Rootmentioning
confidence: 99%